Multi-static spatial and angular studies of polar mesospheric summer echoes combining MAARSY and KAIRA - Chau, Jorge L.; McKay, Derek; Vierinen, Juha; La Hoz, Cesar Augusto Vergara; Ulich, Thomas; Lehtinen, Markku; Latteck, Ralph (Atmospheric Chemistry and Physics, 2018)
Source at https://doi.org/10.5194/acp-18-9547-2018 . Polar mesospheric summer echoes (PMSEs) have been long associated with noctilucent clouds (NLCs). For large ice particles sizes and relatively high ice densities, PMSEs at 3m Bragg wavelengths are known to be good tracers of the atmospheric wind dynamics and to be highly correlated with NLC occurrence. Combining the Middle Atmosphere ALOMAR Radar System (MAARSY) and the Kilpisjärvi Atmospheric Imaging Receiver Array (KAIRA), i.e., monostatic and bistatic observations, we show for the first time direct evidence of limited-volume PMSE structures drifting more than 90km almost unchanged. These structures are shown to have horizontal widths of 5–15km and are separated by 20–60km, consistent with structures due to atmospheric waves previously observed in NLCs from the ground and from space. Given the lower sensitivity of KAIRA, the observed features are attributed to echoes from regions with high Schmidt numbers that provide a large radar cross section. The bistatic geometry allows us to determine an upper value for the angular sensitivity of PMSEs at meter scales. We find no evidence for strong aspect sensitivity for PMSEs, which is consistent with recent observations using radar imaging approaches. Our results indicate that multi-static all-sky interferometric radar observations of PMSEs could be a powerful tool for studying mesospheric wind fields within large geographic areas.